Iron deficiency in soybean. Issue 1 (5th January 2022) - Merry, Ryan; Dobbels, Austin A.; Sadok, Walid; Naeve, Seth; Stupar, Robert M.; Lorenz, Aaron J.
Abstract: Iron deficiency is an important soybean [ Glycine max (L.) Merr.] nutrient deficiency that is easily identified by interveinal chlorosis of the leaves and reduced plant growth, both of which lead to yield reductions. Research in soybean iron deficiency is often segmented into studies on soil characteristics, microbe interactions, specific phenotypes, or genetics of iron efficiency. Joining these areas of research into a comprehensive literature review will advance our understanding of iron deficiency physiology and help to bridge known iron deficiency chlorosis (IDC) resistance loci with plant responses to iron stress. This review investigates what has been accomplished in the areas of phenotyping and genetics of iron deficiency. Furthermore, this work traces iron deficiency physiology research through the plant, beginning with the role of soil, the transport of iron into and through plant tissues, and the eventual deposition in the seed. While IDC is the most phenotyped and genetically mapped trait relating to iron deficiency in soybean, the whole plant is truly affected by and involved in recovery to the stress. While often neglected in iron deficiency research, the soybean–rhizobia relationship is discussed as an area of opportunity for future advancements. Citrate and nicotianamine were identified as important compounds for iron efficiency in several studies and warrant more in‐depth investigation. The aim of this review is to analyze research in soybean iron deficiency phenotyping, genetics, and physiology to reveal connections between these areas and facilitate further discoveries. Core Ideas: Iron deficiency in soybean is a pervasive problem for growers and breeders. Several environmental factors are responsible for iron deficiency in soybean. A gap in understanding exists between IDC QTL and iron deficiency physiology. Iron physiology in soybean is complex and involves the whole plant. Combining knowledge of iron physiology and QTL will lead to improvements of resistance to IDC.